On the design and development of emulation platforms for NFV-based infrastructures. (3rd February 2020) - Garcia, Vinícius Fülber; Souza, Giovanni Venâncio De; Jr., Elias Procopio Duarte; Tavares, Thales Nicolai; Marcuzzo, Leonardo Da Cruz; Santos, Carlos R.P. Dos; Franco, Muriel Figueredo; Bondan, Lucas; Granville, Lisandro Zambenedetti; Schaeffer-Filho, Alberto Egon; Turck, Filip De
Network Functions Virtualisation (NFV) presents several advantages over traditional network architectures, such as flexibility, security, and reduced CAPEX/OPEX. In traditional middleboxes, network functions are usually executed on specialised hardware (e.g., firewall, DPI). Virtual Network Functions (VNFs) on the other hand, are executed on commodity hardware, employing Software Defined Networking (SDN) technologies (e.g., OpenFlow, P4). Although platforms for prototyping NFV environments have emerged in recent years, they still present limitations that hinder the evaluation of NFV scenarios such as fog computing and heterogeneous networks. In this work, we present NIEP: a platform for designing and testing NFV-based infrastructures and VNFs. NIEP consists of a network emulator and a platform for Click-based VNFs development. NIEP provides a complete NFV emulation environment, allowing network operators to test their solutions in a controlled scenario prior to deployment in production networks.